A note on the value of information given asymmetric information and self‐reporting* - PENNO, MARK (Contemporary Accounting Research, 1987)
Abstract. This note demonstrates purely statistical conditions under which a monitor will be valuable in the presence of predecision asymmetric information and self‐reporting. This result is an extension of the information value results found for principal‐agent problems with symmetric information. Résumé. Cette note démontre les conditions statistiques pures sous lesquelles un moniteur sera valable en présence d'une information asymétrique préalable. Ce résultat est un prolongement des résultats de la valeur de l'information obtenus pour des problèmes de mandant‐mandataire avec une information symétrique.